2022
DOI: 10.1021/acs.jpcb.2c06208
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of Cyclophilin D Fine-Tune Its Conformational Dynamics and Activity: Implications for Its Mitochondrial Function

Abstract: Mitochondria are the powerhouse of a cell, whose disruption due to mitochondrial pore opening can cause cell death, leading to necrosis and many other diseases. The peptidyl-prolyl cis–trans isomerase cyclophilin D (CypD) is a key player in the regulation of the mitochondrial pore. The activity of CypD can be modulated by the post-translational modification (PTM). However, the detailed mechanism of this functional modulation is not well understood. Here, we investigate the catalytic mechanism of unmodified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Both serine phosphorylation and lysine acetylation lower the positive charge of the respective target residues, suggesting that these two modifications co-operate to strengthen the interaction with OSCP by changing the electrostatic surface of the interaction site. Moreover, in silico studies suggested that both the phosphorylation of Ser162 ( S191 ) and the acetylation of Lys138 (K166) affects the conformational ensemble of CyPD [ 139 ].…”
Section: Post-translational Modifications Of Cypdmentioning
confidence: 99%
“…Both serine phosphorylation and lysine acetylation lower the positive charge of the respective target residues, suggesting that these two modifications co-operate to strengthen the interaction with OSCP by changing the electrostatic surface of the interaction site. Moreover, in silico studies suggested that both the phosphorylation of Ser162 ( S191 ) and the acetylation of Lys138 (K166) affects the conformational ensemble of CyPD [ 139 ].…”
Section: Post-translational Modifications Of Cypdmentioning
confidence: 99%
“…Cyclophilin D (CypD) is specifically located within the mitochondrial matrix and is an important modulator of mPTP opening. [ 10 12 ] When CypD interacts with other proteins in the mitochondrial membrane, it promotes the opening of the mPTP. [ 13 ] This interaction is particularly influenced by the level of Ca 2+ in the mitochondria.…”
Section: Introductionmentioning
confidence: 99%